Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From North-eastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini) - Rentz, Dcf; Su, You Ning (Zootaxa, 2020)
Four new genera including five new species are described. All are from north-eastern Queensland. Barbaragraecia comprises two new species. B. unicorn Rentz & Su, gen. et sp. nov. (the type species) and B. richardsoni Rentz & Su, sp. nov. Geoffagraecia is known from a single species, G. gwinganna Rentz & Su, sp. nov. the type species. Greenagraecia Rentz & Su, gen. et sp. nov. is known from two species, G. attenuata Rentz & Su, gen. et sp. nov., the type species and G. cooloola Rentz & Su, gen. et sp. nov.. The unrelated genus Nicsara Walker 1869 is discussed and species with falcate ovipositors are removed and placed in a new genus, Larifugagraecia Rentz & Su gen. nov., with Nicsara spuria Redtenbacher 1891 designated as the type species. Two species are removed from Nicsara and placed in Larifugagraecia. These are N. cornuta (Redtenbacher 1891) and N. spuria. Other species remain in Nicsara until they can be further assessed. Biological and ecological notes accompany detailed descriptions of the new species along with many morphological illustrations. Illustrations also are provided for L. spuria gen. nov. A key to the described fully-winged Australian agraeciine genera is provided at the end of the paper.